Real earnings management and firm value using quarterly financial data: Evidence from Korea - Ana Belén Tulcanaza Prieto; Young Hwan Lee (Global Business & Finance Review (GBFR), 2022)
Purpose: This study examines whether real earnings management (REM) affects firm value by introducing quarterly financial data in the Korean market. Design/methodology/approach: The study employed four REM metrics as independent variables, and Tobin's Q as dependent variable. Ordinary least-squares (OLS) panel data regressions were used. To control the endogeneity issue, the two-stage least square (2SLS) regression model was implemented in the analysis. Findings: A significant negative relationship between REM and firm value was found in suspicious firms, whereas no statistically significant relationship was found in non-suspicious firms. Findings revealed that the negative relationship tends to prevail for at least two consecutive quarters. The result of 2SLS regression supports the previous findings that REM activities negatively affect firm value. Research limitations/implications: These results are consistent with the view that managers' opportunistic behavior in terms of REM, may result in decreasing firm values. Mover, the REM effect reverberates not only in the current cash flow from operations (CFO) but also in the next period. Originality/value: Financial regulators need to review carefully the quarterly and annual financial statements to detect firms with relatively high REM activities because these temporarily increased or decreased real activities are underestimated or reversed in subsequent quarters, which reduces earnings sustainability or decreases the firms' performance. The study suggests the implementation of a robust planning and financial-control system in firms to recognize and anticipate the earnings manipulations.
Keywords: 650; Firm value; Real earnings management; Manager's opportunistic behavior